A relação entre complexidade, vigilância e desordem informacional e seu impacto na subjetivação do indivíduo - Siqueira, Fábio Fernandes de (2022)
This research contemplates the relationship between surveillance and disinformation processes in context of network communication complexity. The study recognizes the internet as a system that produces and processes a large volume of information, which makes it a powerful generator of connective intelligence, informational disorder and, above all, increasing complexity. In the web, the surveillance is a native apparatus, part of its network design, that works to enable navigation in the chaos, as well as, to intervene in the way people interact, establishing conversational dynamics and modulating content landscapes. Finally, the study assesses how the relationship between complexity, surveillance and disinformation impacts the individual's subjectivation process, affecting the way they develop memories and knowledge in a new social environment, marked by instability. In this sense, recent episodes, as the Cambridge Analytica case, which occurred during the 2016 American presidential elections, as well as the disinformation occurrences associated with Covid-19 vaccines and the discussions around the Fake News Bill, PL 2.630 (RELATOR..., 2020), exemplify how the research matter has taken shape in the life of modern society